Stable and compact zwitterionic polydiacetylene micelles with tumor-targeting properties. Issue 80 (26th August 2015) - Theodorou, Ioanna; Anilkumar, Parambath; Lelandais, Benoit; Clarisse, Damien; Doerflinger, Anaëlle; Gravel, Edmond; Ducongé, Frédéric; Doris, Eric
Abstract : Stealth zwitterionic polydiacetylene-micelles are evaluated in vivo for the passive targeting of tumors. Abstract : Compact polymerized polydiacetylene-micelles with "stealth" zwitterionic surface coating were assembled and tested in a murine xenograft model of breast cancer. In vivo fluorescence imaging indicated accumulation in the tumor area and histological studies revealed predominant uptake of the micelles at the margins of the tumor, thereby allowing the delineation of its volume.